IMPLEMENTASI VAIC TM TERHADAP PERUSAHAAN ASURANSI NASIONAL - Maheni Ika Sari; Bayu Wijayantini (SEGMEN Jurnal Manajemen dan Bisnis, 2018)
This study aims to clarify the extent of the value of intellectual capital services company and presents an approach for the interpretation of the results. Model value added intellectual coefficient (VAICTM) is used to describe the elements of intellectual capital because this model using financial data. The object of research is the insurance company for a period of four years (2009-2012). The results show the model VAICTM a reliable tool to explain the efficient utilization of intellectual capital. This model can be used by management to assess the performance of the company on their own without relying on the industry standardKeywords: VAICTM , intellectual capital.